2007
DOI: 10.1111/j.1365-2672.2007.03579.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of yogurt and bifidobacteria supplementation on the colonic microbiota in lactose-intolerant subjects

Abstract: Aims:  Colonic metabolism of lactose may play a role in lactose intolerance. We investigated whether a 2‐week supplementation of Bifidobacterium longum (in capsules) and a yogurt enriched with Bifidobacterium animalis could modify the composition and metabolic activities of the colonic microbiota in 11 Chinese lactose‐intolerant subjects. Methods and Results:  The numbers of total cells, total bacteria and the Eubacterium rectale/Clostridium coccoides group in faeces as measured with fluorescent in situ hybrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
99
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(112 citation statements)
references
References 49 publications
3
99
0
4
Order By: Relevance
“…A recent study has shown that a yogurt enriched with B. lactis DN-173010 and B. longum in capsules modifies the composition and metabolic activities of the colonic microbiota and alleviates symptoms in Chinese lactose-intolerant subjects [26] . BIO ® is a fermented milk product which contains a mixture of live bacterial cultures; B. lactis DN-173010 (1.25 × 10 10 cfu/pot) and yogurt starters L. bulgaricus and S. thermophilus (1.2 × 10 9 cfu/pot).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has shown that a yogurt enriched with B. lactis DN-173010 and B. longum in capsules modifies the composition and metabolic activities of the colonic microbiota and alleviates symptoms in Chinese lactose-intolerant subjects [26] . BIO ® is a fermented milk product which contains a mixture of live bacterial cultures; B. lactis DN-173010 (1.25 × 10 10 cfu/pot) and yogurt starters L. bulgaricus and S. thermophilus (1.2 × 10 9 cfu/pot).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent paper of us [6], we describe that inducing the colonic β-galactosidase by administration of yogurt and additional probiotics alleviates the clinical symptoms of lactose intolerance in an adult Chinese population. This suggests a specific role of lactose itself in the development of clinical symptoms.…”
Section: Colonic Fermentation Of Lactosementioning
confidence: 99%
“…Several studies have supplied clinical evidences of the benefits generated by probiotics, as for example in diarrhea treatment (Billooet al, 2006;De Vrese & Marteau, 2007), lactose intolerance (He et al, 2008), irritable bowel syndrome Nagala & Routray, 2011), allergies (Jain et al, 2010), cancer (Chen et al, 2009) and hypercholesterolemia (Baroutkoub, 2010). According to recent meta-analysis based on well conducted clinical trials with probiotics, a clear protective effect was evident, which did not vary significantly between products containing S. boulardii, Lactobacillus rhamnosus GG, L. acidophilus, L. bulgaricus, L. casei, Bifidobacterium longum, B. bifidum var.…”
Section: Introductionmentioning
confidence: 99%